Topological equivalence of finitely determined real analytic plane-to-plane map germs - Skutlaberg, Olav (MATHEMATICA SCANDINAVICA, 2011)
Generic smooth map germs (R^2,0)→ (R^2,0) are topologically equivalent to cones of mappings S^1→ S^1. We carry out a complete topological classification of smooth stable mappings of the circle and show how this classification leads, via the result mentioned above, to a topological classification of finitely determined real analytic map germs (R^2,0)→ (R^2,0).